KEBERLAKUAN KITAB UNDANG-UNDANG HUKUM PERDATA DAN PERAN NOTARIS TERHADAP PEMBUATAN SURAT KETERANGAN WARIS BAGI KETURUNAN TIONGHOA BERAGAMA ISLAM - Octavia Dewi Indrawati; Mohammad Fajri Mekka Putra (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2022)
The purpose of this paper is to examine the enactment of civil law against Chinese descendants who are Muslim and the authority and role of a notary in making a certificate of inheritance for Chinese descendants who are Muslim. This research is a normative legal research using a statutory approach and a conceptual approach. The results of this study are the legal system that can be used by Chinese descendants who are Muslim are free to determine themselves to use the legal system used in making a certificate of inheritance. Notaries have the authority artificially based on Article 1868 of the Civil Code and Article 15 of the UUJN in making a certificate of inheritance for Chinese descendants who are Muslim because Chinese descendants are free to use western law or Islamic law in making the inheritance certificate. However, in making a certificate of inheritance, notaries must apply the precautionary principle so that later it does not cause legal problems.